Does distance e-learning work? A comparison between distance and face-to-face learners using e-learning materials - de Freitas , Sara; Roberts , Gerald P. (Research in Learning Technology, 2003)
This study compares continual assessment data, intake numbers, retention numbers and final examination grades of a mixed cohort of face-to-face and distance learners against similar data from previous years where e-learning materials were not used in order to test whether e-learning materials can support the same quality and quantity of teaching and learning for both face-to-face and distance learners. The results for this cohort of learners demonstrate that: (i) distance e-learners score as well and sometimes better than face-to-face learners; (ii) face-to-face student numbers have increased; (iii) overall, student retention and student attendance have been maintained; (iv) final examination results have been maintained or in some cases improved; (v) lecturer workload was high, but not unmanageable, and it is clear how manageability can be improved. DOI:10.1080/0968776030110307